Framework for Risk Communication and Community Engagement to Improve Vaccine Uptake for COVID-19 and other Vaccine-Preventable Diseases in Low- and Middle-Income Countries (LMIC) - Laston Gonah; Aminata Grace Kobie (Ubiquity Press, 2021)
A framework for guiding risk communication and community engagement (RCCE) during COVID-19 vaccination roll-out is worthwhile in order to guide interventions aimed at improving vaccine uptake. This requires setting up standardised early-warning indicators to predict or detect low uptake; coordination of response activities by all partners, real-time information exchange, innovativeness in designing strategies to deal with arising and anticipated challenges; flexibility to adapt quickly to changing demands and evolving circumstances; and documentation of progress and lessons learnt.